The Paleontological Context : Ichnology - Laza, José Herminio (2020)
Except for some previous records, the first attempts for the study of the lying tracks on sediments started at the beginning of the nineteenth century, as well as the efforts for creating a suitable terminology. Its installation as a scientific discipline began at the end of the nineteenth century. By middle twentieth century, a modern and organized scheme for the classification of ichnofossils and their location in ichnofacies was proposed. Firstly, the only recognized ichnofacies corresponded to marine environments and were defined by bathymetric levels and particular ichnofossils. Immediately, ichnofacies corresponding to transition environments from those marine to continental were identified. In 1985, the ichnological nomenclature became part of the International Code of Zoological Nomenclature. During the 1970s and 1980s, there were papers describing ichnites of continental origin, events that quickly led to the organization of the formal reconnaissance of environments carrying continental tracks, giving rise to successive ichnofacies. Apart from the paleosurfaces, the ichnological content is rich and quite varied in paleosols and so are the tracks of insect nests, solitary or in groups in these paleosols.